2013
DOI: 10.1002/cncy.21310
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of E‐cadherin and zeste homolog 2 expression in endoscopic ultrasound‐guided fine‐needle aspiration of pancreatic adenocarcinoma

Abstract: BACKGROUND: Recent studies have demonstrated that partial or complete loss of E-cadherin (EC) and nuclear accumulation of zeste homolog 2 (EZH2) are hallmarks of poorly differentiated pancreatic adenocarcinoma (PAC). Depletion of EZH2 sensitizes cancer cells to chemotherapy in vitro. The objective of this study was to determine EC and EZH2 expres-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Gao et al 32 reported negative EZH2 expression at 5% in patients diagnosed with pancreatic adenocarcinoma in cell blocks from endosonographic ultrasound-guided fine needle aspirations. In a study of cell blocks from serous effusions, Jiang et al 18 found no EZH2 expression in only 1 patient with metastatic pancreatic adenocarcinoma, and similarly in the current study, no EZH2 expression was found in 1 of the 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al 32 reported negative EZH2 expression at 5% in patients diagnosed with pancreatic adenocarcinoma in cell blocks from endosonographic ultrasound-guided fine needle aspirations. In a study of cell blocks from serous effusions, Jiang et al 18 found no EZH2 expression in only 1 patient with metastatic pancreatic adenocarcinoma, and similarly in the current study, no EZH2 expression was found in 1 of the 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…(1) IHC and special staining IHC can be applied to histologic cores from EUS-FNB, cell block, and even LBC. It can differentiate benign and malignant lesions and reduces false negatives by staining for tumor suppressor gene proteins (e.g., TP53 or E-cadherin) 62 and tumor-associated proteins (e.g., mesothelin, S100P or fascin). 63 Furthermore, IHC can determine tumor aggressiveness or predict the clinical behavior of PNET using the Ki-67 index on large prepared pieces of tumor tissue from EUS-FNB (>2,000 cells).…”
Section: Methods Of Specimen Processing Recommendationmentioning
confidence: 99%
“…Its expression may be used as a prognostic indicator as it is reduced in poorly compared with moderately-differentiated adenocarcinomas48 and reduced expression is an independent predictor of OS in PDAC 48 49. Furthermore, a role for E-cadherin expression in chemotherapy resistance has been established in vitro, as chemoresistant cancer cells have an increased expression of ZEB1 (which represses E-cadherin and regulates EMT) 50.…”
Section: E-cadherin In Human Cancersmentioning
confidence: 99%